Bacteriostatic activity of crude lectins - Kadwadkar, Namrata; Kulkarni, Savita (Pharmacognosy Communications)
Lectins are simply defined as glycoproteins which specifically bind to carbohydrates. Lectins were isolated from Canavalia ensiformis, Phaseolus vulgaris and Ricinus communis using the standard protein precipitation method. The extracted lectins have been characterized using physical and chemical methods including hemagglutination assay and gel electrophoresis for determination of molecular weight. Hemagglutination assay was performed on rat blood cells and human blood erythrocytes of A, B, AB and O positive blood groups. Gel electrophoresis SDS-PAGE analysis was performed and it was found that the Phaseolus vulgaris lectins (PHA-L) was 71.4 kDa, Canavalia lectin was 30.2 kDa and Ricinus communis lectin was 74.4 kDa. The lectins from Canavalia ensiformis, Ricinus communis and Phaseolus vulgaris show good bacteriostatic activity against gram positive bacteria, namely S. aureus, B. subtilis and S. mutans at concentrations of 500 µg/mL and 1 mg/mL when tested by agar-well diffusion method. The colony counting method was also performed which supported the results as with the agar-well diffusion method. A typical agglutination of S. mutans was observed in the presence of the lectins obtained from Canavalia ensiformis and Phaseolus vulgaris.
Keywords: protein precipitation; hemagglutination; molecular weight